Climate, Soil, and Plant Controls on Early-Stage Litter Decomposition in Moso Bamboo Stands at a Regional Scale - Orrego, Marly; Ugawa, Shin; Inoue, Akio; Laplace, Sophie; Kume, Tomonori; Koga, Shinya; Hishi, Takuo; Enoki, Tsutomu (Frontiers in Forests and Global Change, 2022)
Moso bamboo (Phyllostachys edulis) is currently distributed across a wide geographical area in East Asia. As a common bamboo species occurring along a broad environmental gradient, there is a need to understand how environmental and biotic drivers affect belowground processes at large scales. In this study, we investigated the influence of climate, soil properties, stand characteristics, and organic matter input parameters as potential drivers of the initial decomposition process in Moso bamboo stands at a regional scale. Using the Tea Bag Index method, we estimated the initial decomposition rate (k) and stabilization factor (S; potential long-term carbon storage) from standard litter incubated at 13 sites across southern Japan and Taiwan. We found that both decomposition parameters were strongly affected by the climate. The climatic conditions during the incubation period better explained the variance in k. In contrast, the long-term climate was more important for S. Notably, temperature and precipitation interactively affected the initial decomposition rates. This interaction showed that in warmer sites, precipitation increased k, whereas in cooler sites, precipitation had no effect or even decreased k. Soil parameters had no influence on k and only had minor effects on S. A structural equation model showed that the stabilization factor was indirectly affected by stand density, which suggests that higher bamboo densities could increase litter stabilization by increasing above-and below-ground organic matter input. Our study highlights the central role of climate in controlling decomposition processes in Moso bamboo stands on a broad scale. Moreover, differences in stand structure can indirectly affect potential soil carbon storage through changes in organic matter input and soil conditions.